Pemanfaatan Limbah Organik Menjadi Eco-Enzyme Sebagai Solusi Pengelolaan Sampah Dan Edukasi Lingkungan Di Ma Qamarul Huda Badaruddin Bagu, Lombok Tengah - Bq Dina Hardianti; Temi Ainul Safitri; Nora Listantia; Thauhidayatul Hidayah; Rahman; Meiylinda Pomestia (DEDIKASI : Jurnal Pengabdian Kepada Masyarakat, 2024)
This research aims to examine the implementation and effectiveness of a program that utilizes organic waste to create eco-enzymes at Madrasah Aliyah (MA) Qamarul Huda Badaruddin Bagu. This program serves as a strategy for sustainable waste management and an educational tool for environmental awareness. The research employed a descriptive qualitative method, utilizing participatory observation, interviews, and document analysis. The findings indicate that this program has successfully reduced the volume of organic waste at the school, provided natural cleaning products and organic fertilizers, and Increased students' environmental awareness and practical skills. The implementation of the eco-enzyme program at MA Qamarul Huda Badaruddin Bagu can serve as an innovative and effective model for organic waste management for other educational institutions.